The antibacterial effect of Anchovy (Stolephorusinsularis) Extract Against P.aeruginosa - Istien Wardani; Annisa Listya (Denta Journal Kedokteran Gigi, 2020)
Introduction: Root canal infection is largely a continuation of the caries process that is not treated and develops so that it involves the root canal. Sterilization is a part of multivisit root canal treatment and important for the success of root canal treatment. The Anchovy (Stolephorus insularis) contains protein, vitamins (A, B1, C), and minerals (Fe, Ca, K, F). Calcium fluoride (CaF2) contained in anchovies can inhibit bacteria that cannot be removed by chemo-mechanical processes such as instrumentation and irrigation Purpose: The aim of this study was to determine the antimicrobial ability of anchovy extract (Stolephorus insularis) to P. aeruginosa. Materials and Methods: This study was a laboratory experimental research which with post test only control group design. Diffusion method were applied with 2 controls: positive control using ChKM solution, negative control using 1% DMSO and 3 concentrations of jengki anchovy extract (Stolephorus insularis) 18%, 24%, and 30% as treatment groups, where each group consisted of 5 samples. Antimicrobial was assessed by measuring the diameter of the clear zone around the discs contained the anchovy extract (Stolephorus insularis). Data were analyzed by Kruskal-Wallis test followed by Mann-Whitney test. Result: The results from this study showed clear zone around the discs of the anchovy extract (Stolephorus insularis). The more concentration of the extract showed the more antimicrobial zone diameter. The average inhibitory zone at 18% concentration was 6.03 mm, 24% 7.59 mm, 30% 8.69 mm, positive control of ChKM solution 31.43 mm for negative control DMSO 1% 6.03 mm. The largest diameter of the clear zone is at a concentration of 30%. Conclusion: The results obtained showed that the inhibition zone of the Stolephorus insularis extract concentration of 30% had the largest average among the other concentrations of 8.69 mm.